2009
DOI: 10.1029/2008gl037135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variations of cloud and aerosol properties associated with active and break spells of Indian summer monsoon using MODIS data

Abstract: [1] Indian summer monsoon exhibits significant intraseasonal variations with active and break monsoon spells. Using MODIS data of 8 years (2000 -2007), variations of cloud and aerosol properties over the Indian region associated with the active and break spells were examined. The study shows statistically significant variations of cloud properties (cloud optical depth, cloud fraction and cloud top pressure) between active and break monsoon days over central and northeast India and the equatorial Indian Ocean. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Thus there exists a great range of spatial asymmetry of AOD across the country. A maximum value of AOD (of the order of 1.0 or more; Ravi Kiran et al 2009) is observed over the IGP region. Furthermore it is interesting to note that the location of the maximum loading of aerosols during break monsoon condition is located north of but parallel to the climatological position of the monsoon trough.…”
Section: Aerosol Loading and Its Anomalies During Bfa Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus there exists a great range of spatial asymmetry of AOD across the country. A maximum value of AOD (of the order of 1.0 or more; Ravi Kiran et al 2009) is observed over the IGP region. Furthermore it is interesting to note that the location of the maximum loading of aerosols during break monsoon condition is located north of but parallel to the climatological position of the monsoon trough.…”
Section: Aerosol Loading and Its Anomalies During Bfa Casesmentioning
confidence: 99%
“…The red dotted lines represent trajectories at 500 m, the green ones at 1,500 m and the blue lines portray those at 3,000 m. Furthermore, all the three trajectories are originating from the two different locations mentioned above. Thus it can be attributed that the anomalous aerosol loading is due to long range transport plus amplification by local input in a large-scale subsidence backdrop (Ravi Kiran et al 2009). …”
Section: Source Region Of Aerosolsmentioning
confidence: 99%
“…Our speculation is that the type of aerosols and aerosol loading in 2009 as compared to 2008 also played an important role, affecting cloud formation and in turn suppressing precipitation. There is a strong debate that, aerosols cannot play the role of initiators that could trigger long breaks (which accumulate to drought like situation), and that the aerosols and their variability is only an after-effect of the monsoon (aerosol wash out or persistence of aerosol plumes in the absence of precipitation) (Kiran et al, 2009). Though it is true that the drought like conditions cause the observed aerosol variability, it is subject to the time period of study, i.e., if the aerosol variability is investigated after the onset of the monsoon, this assumption is applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Over the Indian region, only a limited number of studies have been done on the aerosol indirect effects. Using MODerate resolution Imaging Spectroradiometer (MODIS) data these studies both qualitatively and quantitatively suggest that there exists a significant positive aerosol indirect effect over IGP and is one of the factors that modulate the Indian summer monsoon (Patra et al, 2005;Ravi Kiran et al, 2009;Panicker et al, 2010). However, it is still uncertain how much the accumulation of aerosols in the non-monsoon months affects the onset and progress of succeeding monsoon season.…”
Section: Introductionmentioning
confidence: 99%